Republic of Slovenia : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines social spending reform and fiscal savings in Slovenia. Rising expenditure has been at the root of Slovenia's fiscal deterioration since the onset of the crisis. The paper explores reform options to reduce Slovenia's social spending over the medium and long term. It discusses key features of the pension system, and analyzes the evolution of pension spending in the absence of reforms. The paper also examines the health and education spending and provides a framework to assess their efficiency relative to other countries.